Tsenguluso ya ndila dza u vha maine wa sialala kha Tshivenda - Ntshauba, Siwethu Thomas (University of Limpopo, 2011)
The mini-dissertation investigated the ways in which one qualifies as a traditional healer in Tshivenda. The study has discovered that a person cannot choose to become a traditional healer, he or she is chosen by the ancestors into this profession and they make their wishes known to the person concerned through continuous illness and dreams. Nowadays, there is an increased number of traditional healers in the community. It seems as if the community is confused as to whether all these healers have gone through the proper ways of becoming a traditional healer in Tshivenḓa or they are largely interested in the economic gain.
Thesis (M.A. (Folklore)) --University of Limpopo, 2011
Keywords: Tranditional healer; Qualification; Ancestors; Healers; Traditional remedicine -- South Africa